(3WHbGJ GdTYQGAs - (3GHf SdGe GdLeMjj , eMeO Hf SdGe Hf YHjOGddg Hf SGde, CHh YHO Gddg GdLeMjj GdHUQj,J (B232 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO CfG CHhWGgQ eMeO Hf CMeO Hf YHOGddg CfG CHhNdjaI GdaVd Hf GdMHGH GdLeMi bGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B41s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B205 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg YGQa MceJ HGdeOjfg GdefhQg (B((3JGQjN (B441) s
Keywords: (3GdJGQjNs